Ways to Reduce the Duration of Study at the University - Gelman, Viktor (Современное образование, 2022)
At present, periods of technological change are becoming comparable to the duration of education in higher education. Therefore, along with the need to use the concept of lifelong education, there is a need to reduce the duration of obtaining basic higher education. Analysis and identification of possible ways to reduce the duration of study at a university while maintaining the required level of graduates' education is the subject of this article. The methodological basis of the work is the integration and generalization of previous studies to improve the effectiveness of training. The article discusses in detail the following complementary ways: changing the content of education and the use of new, more effective teaching methods. It is shown that the reduction of overall time of studying in university while maintaining the required level of education can only be achieved by the joint application of various approaches. The following complementary ways are proposed: changing (optimizing) the content of basic professional knowledge, using more effective teaching methods and individualized learning, reducing auxiliary (transactional) costs for students and increasing the level of motivation of students. More effective teaching methods, in particular, involve improving the lecture system, monitoring progress, and optimizing the speed of introducing new material in group classes. Taking into account the concept of continuous education, a certain fundamental educational background obtained at the university can subsequently be supplemented with short-term modules in the course of additional professional education.